Love and Intimacy in Online Cross-Cultural Relationships The Power of Imagination - Pananakhonsab, Wilasinee; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book challenges assumptions about the motivations that drive women from relatively poor, developing countries to use intermarriage dating sites to find partners from relatively wealthy, developed countries. It is generally assumed that economic deprivation or economic opportunities are the main factors, but this book instead focuses on the work of women's imagination in online cross-cultural relationships, including the role of desire, love and intimacy. The experiences of Thai women are used to explore how they initiate, develop and maintain love and intimacy with Western men across distance and time. The book shows that, in the absence of opportunities to search and meet partners from geographically distant parts of the world, the technology of the internet offers new ways of searching for and managing relationships and has significant consequences for local experiences and expectations of love and partnering. The book will be of interest to scholars and students with an interest in family and intimate life, gender and sexualities, Asian and Thai studies, globalization and nationalism, culture and media, sociology and anthropology. .
1. Introduction -- 2. Motivations behind decisions to pursue cross-cultural relationship online -- 3. Marketing and love: representations of Thai women in the intermarriage market -- 4. Why him?: becoming online daters -- 5. The movement from online to offline relationships -- 6. Love and commitment across distance -- 7. Conclusion. .
Keywords: Ethnicity; Sociology